Port Hinterland Modelling Based on Port Choice - Kramberger, Tomaž; Rupnik, Bojan; Štrubelj, Gregor; Prah, Klemen (Promet - Traffic&Transportation, 2015)
This paper presents a new approach for hinterland modelling based on the results of port choice modelling. The paper follows the idea that the shippers’ port choice is a trade-off between various objective and subjective factors. The presented model tackles the problem by applying the AHP method in order to obtain ports’ preference rates based on subjective factors, and combine them with objective factors, which include port operation costs, sailing times, and land transport costs using MILP. The ports’ hinterlands are modelled by finding the optimal port of choice for different locations across Europe and merging the identical results. The model can be used in order to produce captive hinterland of ports and can also be exploited in order to analyse how changes in the traffic infrastructure influence the size of hinterlands.